Editorial: Special issue: Implementing Pricing Reform in Transport - Korver, Wim; Eijkelenbergh, Pascal (European Journal of Transport and Infrastructure Research, 2003)
Given the current status of research and implementation, the various contributions show that research, and in particular the analysis of the impacts of reforms, must proceed in parallel with implementation, in order to create a virtuous cycle in which research and policy making mutually feed each other. Besides a “window of opportunity” is open for what concerns interurban and urban transport. Several experiences in different European cities confirm that an increasing number of cities are already well into the process of rationalising and increasing the sustainability of their transport systems, notably through the design and implementation of pricing policies. And also for inter-urban transport things are moving, e.g. the proposed revised Eurovignette Directive can be seen as a step in the right direction, although still containing many constraints which would prevent fair and efficient pricing of road freight vehicles. In general it can be said that Social Marginal Cost Pricing is still developing. Most practical experiences only use simple pricing schemes, which are far from optimal prices. In the long term fine-tuning of objectives and schemes will be necessary. Some general recommendations based on several Imprint seminars and the papers presented in this issue.